2001
DOI: 10.1046/j.1432-1033.2001.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular expression and functional characterization of four hyperpolarization-activated pacemaker channels in cardiac and neuronal tissues

Abstract: Hyperpolarization-activated cation currents (I(h)) have been identified in cardiac pacemaker cells and a variety of central and peripheral neurons. Four members of a gene family encoding hyperpolarization-activated, cyclic nucleotide-gated cation channels (HCN1--4) have been cloned recently. Native I(h) currents recorded from different cell types exhibit distinct activation kinetics. To determine if this diversity of I(h) currents may be caused by differential expression of HCN channel isoforms, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
250
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(276 citation statements)
references
References 21 publications
(34 reference statements)
24
250
1
1
Order By: Relevance
“…HCN4 channels activate very slowly and also respond strongly to cAMP [10,11], similar to I h in thalamic relay neurons. HCN3, only recently expressed functionally in HEK293 cells, activates with a time course intermediate between HCN2 and HCN4 [12]. Expression patterns have confirmed that HCN1 expression is restricted to neurons of the neocortex, hippocampus, cerebellar cortex and brainstem nuclei [7,13,14].…”
Section: Introductionmentioning
confidence: 71%
“…HCN4 channels activate very slowly and also respond strongly to cAMP [10,11], similar to I h in thalamic relay neurons. HCN3, only recently expressed functionally in HEK293 cells, activates with a time course intermediate between HCN2 and HCN4 [12]. Expression patterns have confirmed that HCN1 expression is restricted to neurons of the neocortex, hippocampus, cerebellar cortex and brainstem nuclei [7,13,14].…”
Section: Introductionmentioning
confidence: 71%
“…In the sinoatrial node, in all species analyzed so far (e.g. rabbit, guinea pig, mouse and dog) HCN4 is the major isoform, accounting for about 80 % of I h [11,109]. The remaining fraction of this current is species-dependent.…”
Section: Regulation Of Hcn Channelsmentioning
confidence: 98%
“…This specific molecular marker for the pacemaker [39] is expressed as early as E7.5 in the cardiac crescent, becoming restricted to the sinus horns of the sinus venosus and eventually to the SAN region by E12.5 [16]. Hcn4-mutant mice die at midgestation stage due to the lack of formation of a ''mature'' pacemaker, whereas its overexpression mimics pacemaker properties in cell cultures [26,31,39,40,48]. Nppa (also known as ''atrial natriuretic factor'' [ANF]), which is expressed in atrial myocytes, is a chamber differentiation marker and is absent in the pacemaker; the T-box transcription factor Tbx3, has been reported to be specifically expressed in the cardiac conduction system, including the SAN [21].…”
Section: Introductionmentioning
confidence: 99%